The Effect of Market Timing Ability and Fund Size on Mutual Fund Performance of Mutual Fund Companies in Indonesia - Mochammad Arif Budiono; Musdalifah - Azis (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
This study aims to analyze the effect of market timing ability and fund size of mutual funds on the performance of equity funds. This research was conducted at a mutual fund company registered in the Financial Services Authority (OJK) 2018-2019 period. This study uses purposive sampling with a total sample of 65 mutual fund shares. The type of data used is quantitative data and data sources in the form of company annual financial statements. Data analysis tools used are descriptive statistics and panel data regression. The results of this study indicate that the market timing ability has a significant positive effect on the mutual fund performance and the fund size has a significant negative effect on the mutual fund performance.